2014
DOI: 10.1002/cne.23514
|View full text |Cite
|
Sign up to set email alerts
|

DCX‐expressing cells in the vicinity of the hypothalamic neurogenic niche: A comparative study between mouse, sheep, and human tissues

Abstract: Neural stem and precursor cells persist postnatally throughout adulthood and are capable of responding to numerous endogenous and exogenous signals by modifying their proliferation and differentiation. Whereas adult neurogenesis has been extensively studied in the dentate gyrus of the hippocampal formation and in the subventricular zone adjacent to the wall of the lateral ventricles, we and others have recently reported constitutive adult neurogenesis in other brain structures, including the hypothalamus. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 70 publications
3
115
1
1
Order By: Relevance
“…GFAP is expressed by not only astrocytes but also tanycytes in the CVOs (Robins et al 2013;Batailler et al 2014). The density of the GFAP-positive astrocytes/tanycytes was apparently higher at distal subdivisions of the sensory CVOs as compared with central subdivisions; the lateral zone (vs capillary plexus) in the OVLT (Fig.…”
Section: Vascular Permeability Of Blood-derived Moleculesmentioning
confidence: 92%
“…GFAP is expressed by not only astrocytes but also tanycytes in the CVOs (Robins et al 2013;Batailler et al 2014). The density of the GFAP-positive astrocytes/tanycytes was apparently higher at distal subdivisions of the sensory CVOs as compared with central subdivisions; the lateral zone (vs capillary plexus) in the OVLT (Fig.…”
Section: Vascular Permeability Of Blood-derived Moleculesmentioning
confidence: 92%
“…Here, dentate DCX expression was used as surrogate marker of neurogenesis (Couillard-Despres et al, 2005), to examine the impact of increasing age on total numbers of late progenitor cells (neuroblasts) and immature postmitotic newborn neurons. It should be mentioned however that DCX expression is not limited to the "canonical" neurogenic regions (hippocampus and SVZ/olfactory bulb) as DCXþ cells have been described in the adult striatum, corpus callosum, piriform cortex, amygdala, and hypothalamus (Batailler et al, 2014;Klempin et al, 2011;Marlatt et al, 2011;Martí-Mengual et al, 2013;Saaltink et al, 2012;Zhang et al, 2009).…”
Section: Total Dcxþ Cellsmentioning
confidence: 97%
“…Recently, studies have suggested the presence of adultneurogenesis in the hypothalamus (Batailler et al, 2014;Saaltink et al, 2012), involved in maintaining weight and metabolism (Lee and Blackshaw, 2012). To determine Figure 1 In the absence of stress, genetically increasing adult hippocampal neurogenesis in iBax mice increases adult hippocampal neurogenesis, but does not affect anxiety-and antidepressant-responsive behavior.…”
Section: Genetic Deletion Of Bax Increases Adult Hippocampal Neurogenmentioning
confidence: 99%